The Role of the Principal in Designing Marketing Strategies During the Admission of New Students - Nasywa Nurhasanah Ramadhani; Rubini (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2026)
This study aims to analyze the role of school principals in designing and implementing educational marketing strategies at Tafaqquh Fiddin Kindergarten during the New Student Admission (PPDB) period. The research is motivated by the high competition of Early Childhood Education (PAUD) institutions in the Cisauk area, Tangerang Regency, so schools are required to have innovative and adaptive marketing strategies. The research uses a qualitative approach with a case study type. The research informants consisted of the principal, three teachers, two parents of students, and one foundation administrator who were selected through purposive sampling techniques. Data collection was carried out through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawn. The results of the study showed that the principal implemented a marketing strategy based on segmentation, targeting, and positioning by highlighting the identity of the sunnah school based on tahfidz and salafiyah. The marketing strategy is carried out through strengthening the tahfidz flagship program, implementing all-in fees, using Instagram and WhatsApp social media, and strengthening relationship marketing through intensive communication with parents. The novelty of this research lies in the existence of a free screening program for prospective students as a psychological approach in the marketing of Islamic-based early childhood education. In addition, marketing success is also supported by the quality of human resources, school facilities, and a fun play-based learning process. This study concludes that the marketing of modern education in Islamic PAUD institutions is not only oriented towards promotion, but also on the development of image, service quality, and emotional relationships with the community in a sustainable manner.